Reymont Iwaszkiewicza - Gędas, Katarzyna; Iwaszkiewicz, Jarosław (Colloquia Litteraria, 2020)
The author explores the reception of Wladyslaw Reymont’s writings in Jaroslaw Iwaszkiewicz’s literary critique, looking at his memoirs, diaries, the reviews he wrote, his correspondence and literary works. The article also features a translation and edition of Iwaszkiewicz’s article Un douloureux anniversaire. Stefan Zeromski et Wladyslaw Reymont - hitherto unpublished in Polish - which first appeared in the francophone monthly ‘Pologne Litteraire’ in 1926 (no. 2).